2004
DOI: 10.1021/nl025861f
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ionic Liquids as Template to Monolithic Mesoporous Silica with Wormlike Pores via a Sol−Gel Nanocasting Technique

Abstract: This paper reports a novel room-temperature ionic liquid (RTIL), [C4mim]+ BF4 -, as template to monolithic mesoporous silica with wormhole framework via a convenient nanocasting technique. In contrast with the applied liquid crystal self-assembly of long-chain surfactants on the preparation of mesoporous nanostructures, a new so-called hydrogen bond-co-π−π stack mechanism was proposed to be responsible for the present self-assembly of the RTIL in the reaction system for the formation of the wormlike mesopore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
411
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(434 citation statements)
references
References 25 publications
19
411
2
2
Order By: Relevance
“…The first ionogel (for gel synthesized with an IL) was obtained in 2000 by Dai et al (2000). Several investigations led to a variety of materials (Vioux et al, 2010;Karout et al, 2007;Klingshirn et al, 2005) implying numerous characterizations: porous volume, fractal dimension, conductivity of the ionogel bulk measured with two plate electrodes (Gupta et al, 2012;Neouze et al, 2006;Karout et al, 2009aKarout et al, , 2009bZhang et al, 2010;Zhou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The first ionogel (for gel synthesized with an IL) was obtained in 2000 by Dai et al (2000). Several investigations led to a variety of materials (Vioux et al, 2010;Karout et al, 2007;Klingshirn et al, 2005) implying numerous characterizations: porous volume, fractal dimension, conductivity of the ionogel bulk measured with two plate electrodes (Gupta et al, 2012;Neouze et al, 2006;Karout et al, 2009aKarout et al, , 2009bZhang et al, 2010;Zhou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Nanostructures (nanoparticles, nanowires, and nanobelts) of complex oxides have attracted much attention because of their size-induced novel properties. Although some synthesis methods are successful for fabricating single-cation oxide nanocrystals, [7][8][9][10][11][12][13][14] only a limited amount of work is available for synthesizing nanostructures of complex oxides (with two or more types of cations) because of difficulties in controlling the composition, stoichiometry, and/or crystal structure. The existing techniques rely on high pressure, salt-solvent-mediated high temperature, surface-capping agent, or organometallic precursormediated growth process, [15][16][17][18][19][20][21][22][23][24] and the types of oxides that can be synthesized are rather limited.…”
mentioning
confidence: 99%
“…Development of mesoporous silica is not limited to long chain imidazolium based ILs. Zhou et al and Zhang et al utilize 1-butyl-3-methylimidazolium tetrafluoroborate (C 4 MimBF 4 ) to synthesize mesoporous silica via a new mechanism, known as hydrogen bond-co-π-π-stack [1,32]. Despite these many researches conducted on usage of ILs as template, only one research was able to use ILs to develop MSNs and in this research, it was found that MSNs morphology are dependent on the type of ILs used [33].…”
Section: Introductionmentioning
confidence: 79%